North cyprus: Tourism and the challenge of non-recognition - Warner, Jonathan (My University, 1999)
Since 1974, the Mediterranean island of Cyprus has been divided. The southern, Greek sector has benefited from international recognition as the Republic of Cyprus, and is generally much more developed than the unrecognised Turkish sector in the north. A boom in construction and environmental degradation has accompanied the rapid growth of southern Cyprus as a tourist destination. The large numbers of visitors are now viewed less positively than before, and the number of complaints by holidaymakers about noise and other forms of pollution is increasing. In contrast, northern Cyprus has been slow to develop, giving an important opportunity to the Turkish Cypriot community to avoid the pitfalls of the south.The growth of interest in alternative forms of tourism worldwide presents an opportunity for development to take place even where political problems exist, and to be both environmentally sensitive and profitable. This paper explores the possibilities currently available to the Turkish Cypriots, and recommends that resources should be switched from traditional ’sun, sand and sea' tourism towards alternative types. Some of the obstacles towards the implementation of a sustainable tourism strategy are also examined. © 1999, Taylor & Francis Group, LLC. All rights reserved.
Keywords: tourism development; tourist behavior; tourist destination; Cyprus